The Effectiveness Off Counseling On Drug Compliance in Hypertension Patients at Babelan I Public Health Center in 2022 - Mahajer Saipuloh Anwar; Cusmarih Cusmarih (Malahayati Nursing Journal, 2022)
ABSTRACT Hypertension is a disease that is familiar to the world’s population and the local community. Hypertension is also known as high blood pressure. Ussually hypertension is defined as pressure above 140/90, and is considered severe if the pressure is above 180/120.Data from the World Health Organization (2015) about 1.13 billion people in the world suffer from hypertension. West Java is the province with the lowest prevalence of hypertension on the island of Java, which is 29.4%. According to the highest prevalence is found in North Bekasi with 23.85% - 35.65% Adherence to takingmedication for patients with hypertension is important because hypertension is a disease that cannot be cured but must always be controlled so that complications do not occur which can lead to death. To find out whether there is an effectiveness of counseling on medication adherence in hypertension patients at the Babelan I Public Health Center. The research method used is descriptive analytical with a cross-sectional approach, sampling using non-probability sampling with purposive type aside. Populan in this panelman is hypertensive patiens who do nt regularly take medication as many as 73 respondents, after entering into the slovin formula the number of samples is 62 respondents. Data collection uses a questionnaire. Bivariate analysis using i chi square. From the Chi Square statistical test results obtained p value of 0.000 it can be concluded that p value (0.000) a value (0.05), this shows that there is Counseling Effectiveness on ninum Gear Compliance in Hypertensive Patiens at the Babelan I Health Center. There is a Significant effectiveness between counseling on adherence taking medication for hypertensive patients at the Babelan Helth Center.  Keywords: Hypertension, Counseling, Compliance with Taking Medication  ABSTRAK Penyakit hipertensi ini merupakan penyakit yang tak asing lagi ditelinga penduduk dunia dan masyarakat setempat. Hipertensi disebut juga dengan nama tekanan darah tinggi. Biasanya hipertensi didefinisikan sebagai tekanan di atas 140/90, dan dianggap parah jika tekanan diatas 180/120. Data WHO (World Health Organization) tahun 2015 sekitar 1.13 miliar orang di dunia menderita hipertensi. Jawa barat merupakan provinsi dengan prevalensi hipertensi paling tinggi di pulau jawa yaitu sebesar 29,4%. Prevalensi tertinggi ditemukan di Bekasi Utara dengan 23,85% – 35,65%. Kepatuhan minum obat penderita hipertensi merupakan hal penting karena hipertensi merupakan hal penting karena hipertensi merupakan penyakit yang tidak dapat disembuhkan tetapi harus selalu dikontrol atau dikendalikan agar tidak terjadi komplikasi yang dapat berujung pada kematian. Untuk mengetahui apakah ada efektivitas konseling terhadap kepatuhan minum obat pada pasien hipertensi di Puskesmas Babelan I. Metode penelitian yang digunakan adalah deskriptif analitik dengan pendekatan cross sectional pengambilan sampel menggunakan non probability sampling dengan jenis purposive sampling. Populasi dalam penelitian ini adalah penderita hipertensi yang tidak patuh akan minum obat sebanyak 73 responden, setelah dimasukan ke dalam rumus slovin jumlah sampelnya sebanyak 62 responden. Pengambilan data menggunakan kuesioner. Analisis secara bivariate dengan menggunakan uji chi square. Dari hasil uji statistik Chi Square diperoleh p value sebesar 0,000 dapat disimpulkan p value (0,000) nilai a (0,05), hal ini menunjukan bahwa ada Efektivitas Konseling Terhadap Kepatuhan Minum Obat Pada Pasien Hipertensi Di Puskemas Babelan I. Ada Efektivitas yang bermakna antara konseling terhadap kepatuhan minum obat pada pasien hipertensi di Puskemas Babelan 1. Kata Kunci: Hipertensi, Konseling, Kepatuhan Minum Obat